Factors associated with offer and uptake of provider-initiated HIV testing and counselling among men attending healthcare facilities in Moshi Municipality, Northern Tanzania. - Hellen Kyilyosudu; Sia E Msuya; James S Ngocho; Damian J Damian (PLoS ONE, 2023)
Background HIV Testing and Counseling is a critical entry-point for HIV care, treatment and prevention. Tanzania adopted the WHO recommendations of Provider-Initiated HIV Testing and Counseling (PITC) in 2007 with the aim of increasing early HIV diagnosis and timely access to treatment and support services. However, approximately 55% of men are still unaware of their HIV status. This study aimed to determine the level of PITC uptake and factors associated with PITC availability and uptake among men attending healthcare facilities in Moshi Municipality, Northern Tanzania. Method A facility-based cross-sectional study was conducted in July 2019 in five selected healthcare facilities in Moshi Municipal, Kilimanjaro region. Exit interviews were conducted with men aged 18 years and above who attended for care in the selected facilities. Modified Poisson regression modelling with robust standard errors were used to determine factors independently associated with being offered and accepting the PITC offer. Results A total of 562 men participated in this study. The median age of participants at enrollment was 37 (IQR: 26-59) years. Only 58% of participants reported to have been offered provider-initiated HIV counseling. Of these, 83% accepted the offer of HIV testing. Age between 35-59 years (aPR = 1.2; 95% Confidence Interval (CI): 1.0, 1.4; p = 0.033) and having primary education (aPR = 0.7; 95% CI: 0.6, 0.9; p = 0.010) were factors independently associated with being offered PITC. Age between 35-59 years (aPR = 0.8; 95% CI: 0.7, 0.9; p = 0.002); having been previously tested for HIV (aPR = 1.3; 95% CI: 1.1, 1.5; p = 0.011) and visiting a health facility twice or more in previous year (aPR = 1.3; 95% CI: 1.2, 1.5; p<0.001) were independently associated with uptake of HIV testing. Conclusion Despite high PITC uptake, about 2 in 5 men attending healthcare facilities in Moshi municipality were not offered the service. Providers should target men aged ≤ 34 years, with primary education, visiting facilities for the first time and who have never been tested for HIV.